VEHICULAR HEAD-UP DISPLAY SYSTEM USING VIRTUAL IMAGE AT DIFFERENT DISTANCES - LIN SHIMING; LIN YIH-MING; QIN ZONG; LUO KUANG-TSO (2022)
To provide a vehicle head-up display system which provides a driver with two virtual images of different image distances.SOLUTION: Each of virtual images utilizes all of pixels in a single image source 10. A linearly polarized light beam 11 emitted from the image source passes through a dynamic polarization converter 12. Thereby, two image light beams 13 of orthogonal polarization states are formed which are rapidly switched in time division multiplexing. The two image light beams are respectively selected for transmission and reflection by a polarization selection component 14. The reflected image light beam is handled by an optical relay component to form an intermediate image. A curved mirror 64 reflects the two image light beams to a virtual image reflecting surface and forms two virtual images of different virtual image distances relative to driver's eyes in front of the virtual image reflecting surface.SELECTED DRAWING: Figure 1 【課題】車両用ヘッドアップ表示システムは、運転者に、異なる画像距離の２つの虚像を提供する。【解決手段】虚像の各々は、単一の画像ソース１０における全てのピクセルを利用する。画像ソースから発せられた直線的に偏光した光ビーム１１は、動的偏光変換器１２を通過する。それによって、時分割多重化で迅速に切り替えられる、直交する偏光状態の２つの画像光ビーム１３を形成する。２つの画像光ビームは、偏光選択構成要素１４によって、透過及び反射をそれぞれ選択される。反射した画像光ビームは光中継構成要素によって扱われ、中間画像を形成する。曲面鏡６４は２つの画像光ビームを虚像反射面に反射し、虚像反射面の前における運転者の目に対して、異なる虚像距離の２つの虚像を形成する。【選択図】図１